2001
DOI: 10.4049/jimmunol.166.5.3542
|View full text |Cite
|
Sign up to set email alerts
|

IL-13-Induced Airway Hyperreactivity During Respiratory Syncytial Virus Infection Is STAT6 Dependent

Abstract: Airway damage and hyperreactivity induced during respiratory syncytial virus (RSV) infection can have a prolonged effect in infants and young children. These infections can alter the long-term function of the lung and may lead to severe asthma-like responses. In these studies, the role of IL-13 in inducing and maintaining a prolonged airway hyperreactivity response was examined using a mouse model of primary RSV infection. Using this model, there was evidence of significant airway epithelial cell damage and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 61 publications
10
109
4
Order By: Relevance
“…Similarly, Grunig et al (8) demonstrated that administration of either rIL-13 or rIL-4 to rag 1-deficient mice induced AHR, and the effects of these cytokines were mediated through an IL-4 receptor ␣-chaindependent pathway. These studies, demonstrating overlapping or complementary roles for IL-4 and IL-13 in the induction of AHR, are consistent with those using STAT6-deficient mice, which lack IL-4 and IL-13 signaling pathways and which do not develop AHR (19,20).…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, Grunig et al (8) demonstrated that administration of either rIL-13 or rIL-4 to rag 1-deficient mice induced AHR, and the effects of these cytokines were mediated through an IL-4 receptor ␣-chaindependent pathway. These studies, demonstrating overlapping or complementary roles for IL-4 and IL-13 in the induction of AHR, are consistent with those using STAT6-deficient mice, which lack IL-4 and IL-13 signaling pathways and which do not develop AHR (19,20).…”
Section: Discussionsupporting
confidence: 73%
“…We also showed that the number of PAS-positive cells, goblet cells and STAT6 is well known to be a critical transcriptional factor for IL-13 and IL-4 signaling [29,30]. A previous report [11] suggested that IL-13 induces the expression of IL-13Rα 2 in bronchial epithelial cells, which was STAT6-dependent.…”
Section: Western Blot Analysis Of Stat6 and P-stat6mentioning
confidence: 85%
“…It has already been shown that CD8 + T cells are necessary to cause airway hyperresponsiveness during respiratory syncytial virus infection (RSV) [40]. It has also been shown that IL-13 is produced during the response to RSV, and that blocking IL-13 causes a reduction in AHR induced upon infection [41]. Thus, it may be that CD8 + T cells play the primary role in viral exacerbation of asthma.…”
Section: Discussionmentioning
confidence: 99%